Biodigestão anaeróbica do resíduo da produção de cogumelos tipo champignon de Paris (Agaricus bisporus) - Vieira, Sabrina (2021)
Population and economic growth is directly linked to the increased demand for food and energy, and the generation of waste. Anaerobic digestion is a process that makes it possible to treat waste and produce biogas, which can be applied to generate electricity. Mushroom consumption is on the rise in Brazil and is an expanding economic activity. Paris champignon mushrooms (Agaricus bisporus) are the most consumed in Brazil and worldwide. Its production is made by fermentation in the solid state using lignocellulosic materials, and the process yield varies between 2025%, which means that a large volume of solid waste is generated at the end of the process. This residue is still rich in organic matter and generally undergoes composting so that it can be applied (or marketed) as fertilizer. The production of champignon mushrooms requires intense temperature control and refrigeration of the final product until commercialization, resulting in considerable energy expenditure. This work aimed to study the feasibility of carrying out the anaerobic biodigestion of the spent substrate for the production of mushrooms of the Paris champignon type (Agaricus bisporus) as a way of producing electric energy from biogas, reducing production costs. The depleted substrate was donated by a mushroom producer in the Campos Gerais region (Paraná). The physicalchemical characterization of the residue was carried out by determining total solids, volatile solids, carbon, nitrogen and lignocellulosic compounds. The determination of the biochemical methane potential (BMP) was carried out according to the methodology of the German standard VDI4630, reaching a value of 157.38 LCH4/kgsvt and a CH4 content of 51.44% in biogas. The economic feasibility of installing a biogas production plant from this waste, aiming at saving electricity and digestate commercialization, which was evaluated through two case studies involving a property located in the city of Castro/PR and another in Arraial D'Ajuda/BA. The case studies were carried out using the BiogásInvest tool, which showed that the transformation of the mushroom residue into energy is feasible in one of the properties, however in the other it depends on the commercialization of digestate as a biofertilizer. It can be seen that the use of waste from the production of Agaricus bisporus for biogas is efficient, and has the potential to be explored to promote the circular economy in the mushroom production chain.